EVOLUTION, INFORMATION AND SEMIOTIC INTELLIGENCE. - Lee, J. Scott (Journal of Interdisciplinary Studies, 2025)
In The Machines of Evolution and the Scope of Meaning, Gary Tomlinson uses a Piercean framework of signs within the context of the "extended evolutionary synthesis." The search for cardinal terms in the evolutionary lexicon leads to "first principles." An extended evolutionary hypothesis opens up "processual" views of biological phenomena; for example, genes are invoked or retarded in their operations through their molecular surroundings and momentary environment. Reflexivity between organism and environment and within the brain of some species makes an intellectual space for the machines of the title to operate as "abstract" schemata of highly generalizable algorithms of evolution. These include natural selection, niche construction, the "blind probe head" (the molecular interaction between niche and organism), and the fourth, or "semiotic," machine. In that machine Tomlinson probes species that use meaning--for example, songbirds--and species that do not--bees. The book closes on questions of meaning in other species, human meaning with tools, and traditions that chimp groups share. This latter expands our notions of teaching and learning for both humanists and evolutionary biologists.